Market Segmentation and Stock Prices: Evidence from an Emerging Market - DOMOWITZ, IAN; GLEN, JACK; MADHAVAN, ANANTH (Journal of Finance, 1997)
ABSTRACT We examine the relationship between stock prices and market segmentation induced by ownership restrictions in Mexico. The focus is on multiple classes of equity that differentiate between foreign and domestic traders, and between domestic individuals and institutions. Significant stock price premia are documented for shares not restricted to a particular investor group. We analyze the theoretical and empirical determinants of premia across firms and over time. In addition to economy‐wide factors, segmentation reflects the relative scarcity of unrestricted shares. The results provide additional support for Stulz and Wasserfallen's (1995) hypothesis that firms discriminate between investor groups with different demand elasticities.